Galicia in the realm of Habsburg mythology - Tomasz Gąsowski (Folia Historica Cracoviensia)
The disappearance, breakup, or perhaps the dissolution of the Habsburg monarchy into nonexistence in the last several days of the “Great War” did not mean that time and history disappeared without a trace. For it left a rich and varied heritage that consists of intertwined collective and cultural memories that transform over time into a mythology. An important place in that Central-European, Habsburg mythology is taken by the myth of Galicia. Evidence of its existence and vitality is its emergence several years ago, as unexpected as it was intensive, in the commercial realm. That was made possible by falling back onto heritage, remembrance, and myth, and not by – even an elementary – knowledge of the reality under this banner. The Kingdom of Galicia was wiped out from the territory it used to occupy by the disaster of two wars. Yet a memory of it, evidently strongly rooted, managed to survive that unfavourable time and today it is still very much alive, even though much transformed. The time that has passed, together with all the historical tremors during that time, has resulted in a kind of deconstruction from which a new, mythical form of Galicia emerged. It began to live its own peculiar life which has hardly anything in common with the original. The realm in which its presence is best visible today is what can broadly be called “commercial use”. The cultivation of the current, predominantly commercial functionality of Galicia is only rarely accompanied by a reflection on the sense or reason for the cherishing of its mythology, which is what is actually taking place. Are the material benefits – because there must be some – a sufficient justification for the glorification of the Austrian partition in contemporary Poland?